On relaxed LMI-based designs for fuzzy regulators and fuzzy observers - Teixeira, Marcelo C. M. [UNESP]; Assunção, Edvaldo [UNESP]; Pietrobom, Hilton C. (Institute of Electrical and Electronics Engineers (IEEE), 2001)
Relaxed conditions for the stability study of nonlinear, continuous systems given by fuzzy models are presented. A theoretical analysis shows that the proposed method provides better or at least the same results of the methods presented in the literature. Digital simulations exemplify this fact. These results are also used for the fuzzy regulators and observers design. The nonlinear systems are represented by the fuzzy models proposed by Takagi and Sugeno. The stability analysis and the design of controllers are described by LMIs (Linear Matrix Inequalities), that can be solved efficiently by convex programming techniques. The specification of the decay rate, constraints on control input and output are also described by LMIs. Finally, the proposed design method is applied in the control of an inverted pendulum.
Keywords: Fuzzy control; LMIs; nonlinear systems; observers; regulators